2009
DOI: 10.1017/s1355617709090237
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age and sex on clustering and switching during speeded verbal fluency tasks

Abstract: Past research has been inconsistent with regard to the effects of normal aging and sex on strategy use during verbal fluency performance. In the present study, both Troyer et al.'s (1997) and Abwender et al.'s (2001) scoring methods were used to measure switching and clustering strategies in 60 young and 72 older adults, equated on verbal ability. Young adults produced more words overall and switched more often during both phonemic and semantic fluency tasks, but performed similarly to older adults on measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
77
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 44 publications
(98 reference statements)
16
77
1
7
Order By: Relevance
“…Our fi ndings regarding the UVFT task cannot be compared with previous studies because we could not fi nd other studies with healthy populations. In terms of the total time to complete the PVFT task, several studies have confi rmed our fi ndings regarding the age effect (Bryan et al, 1997;Lanting et al, 2009). Concerning the factors that may have an infl uence on or mediate the relation between age and the PVFT task, there is evidence supporting that verbal knowledge (mediated also by educational level) is not able to compensate for age-related cognitive declines (Bryan et al, 1997).…”
Section: Age Effects In Verbal Fluency Task Performancesupporting
confidence: 70%
See 2 more Smart Citations
“…Our fi ndings regarding the UVFT task cannot be compared with previous studies because we could not fi nd other studies with healthy populations. In terms of the total time to complete the PVFT task, several studies have confi rmed our fi ndings regarding the age effect (Bryan et al, 1997;Lanting et al, 2009). Concerning the factors that may have an infl uence on or mediate the relation between age and the PVFT task, there is evidence supporting that verbal knowledge (mediated also by educational level) is not able to compensate for age-related cognitive declines (Bryan et al, 1997).…”
Section: Age Effects In Verbal Fluency Task Performancesupporting
confidence: 70%
“…A great majority of studies found an age-related decline in performance of phonemic and semantic VFT, as demonstrated by the metanorms of Loonstra, Tarlow and Sellers (2001), in accordance with fi ndings from further research (Bryan, Luszcz, & Crawford, 1997;Butman, Allegri, Harris, & Drake, 2000;Lanting, Haugrud, & Crossley, 2009;Peña-Casanova et al, 2009). Conversely, there is evidence of an education effect, showing that highly educated outperform low education individuals (Buriel, Gramunt Fombuena, Böhm, Rodés, & Peña-Casanova, 2004;Butman et al, 2000;Kosmidis, Vlahou, Panagiotaki, & Kiosseoglou, 2004;Peña-Casanova et al, 2009;Rami, Serradell, Bosch, Villar, & Molinuevo, 2007;Van Der Elst, Van Boxtel, Van Breukelen, & Jolles, 2006;Villodre et al, 2006).…”
supporting
confidence: 66%
See 1 more Smart Citation
“…However, some studies of young adults [11][12][13][14][15] , elderly and neurological diseases 16,17 , provided data regarding the abilities of clustering and switching of these populations, arguing that this analysis provides aditional information in regard to the cognitive flexibility, executive function and lexical organization. There is no normative data for these parameters for Brazilian Portuguese.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found in young adults without conditions, total words recalled that varied between 14.0 and 26.2 on average in the semantic test, and 9.5 and 15.1 in phonological test; already for the average cluster size, the values range between 0.75 and 1.7 for semantics, and phonological between 0.24 and 1.4. The number of switches varies in studies between 7.0 and 11.6 for the group "animals" and between 7.9 and 10.55 for letters 12,[14][15][16][17][18] . Regarding the comparative performance of the two tests and the factors determining the results, there is greater agreement in the literature, and in this study has obtained similar data to studies cited, even analysing itself a different population.…”
Section: Discussionmentioning
confidence: 99%